Kualitas Produk Olahan Tomat Untuk Meningkatkan Minat Beli Konsumen Pada UMKM Di Desa Kotapulu Kecamatan Dolo Kabupaten Sigi - Siti Handayani R. Dahab; Farid Farid; Anisah Anisah (Universitas 45 Surabaya, 2023)
This service activity aims to add insight and knowledge to business actors regarding product quality to increase consumer buying interest in their products with the importance of labeling, packaging and marketing in order to increase added value, profit and product sales. MSMEs in Kotapulu village are quite developed, but the packaging and labels used are still very simple, the marketing techniques used are also not optimal, they only market to stall owners and market traders around the village. The method used in this activity is brief counseling and training. The purpose of implementing this community service activity is to introduce through counseling and training activities to MSMEs in Kotapulu village so that they can become more familiar with product labeling and packaging as well as good and attractive marketing techniques so as to increase consumer buying interest.